METEOROLOGICAL EFFECTS ON COSMIC RAY INTENSITY AND THE MESON SPECTRUM - Rose, D. C. (Canadian Journal of Physics, 1951)
Continuous recording of the intensity of the hard component of cosmic rays has been carried out at Ottawa (Geomagnetic Lat. 56.8) and at Resolute (Geomagnetic Lat. 83) in the Canadian Arctic for over a year. Two counter telescopes with different amounts of lead shielding are used at each station. The results have been analyzed for barometer effect in four series of observations each extending over three months. When averaged, they show a barometer coefficient of –1.75% per cm. of mercury for mesons with momenta above 350 Mev./c and –2.13% per cm. of mercury for those with momenta above 630 Mev./c.A calculation has been made of the temperature and barometer effects. It was based on the variations in the probability of decay of mesons in the atmosphere, under varying atmospheric conditions. The calculations of the temperature effect do not yield results comparable with measurement; those of the barometer effect show that considerable information can be obtained about the meson spectrum from measurements of the barometer coefficients. The results favor a spectrum in agreement with parts of spectra measured by other authors. They suggest the possibility of a second maximum in the production spectrum of mesons.